Placing the Public in Public Health in Post-War Britain, 1948-2012 - Mold, Alex (Medicine and Biomedical Sciences in Modern History, 2019)
This open access book explores the question of who or what 'the public' is within 'public health' in post-war Britain. Drawing on historical research on the place of the public in public health in Britain from the establishment of the National Health Service in 1948, the book presents a new perspective on the relationship between state and citizen. Focusing on health education, health surveys, heart disease and the development of vaccination policy and practice, the book establishes that 'the public' was not one thing but many. It considers how public health policy makers and practitioners imagined the public or publics. These publics were not mere constructions; they had agency and the ability to 'speak back' to public health. The nature of publicness changed during the latter half of the twentieth century, and this book argues that the relationship between the public and public health offers a powerful lens through which to examine such shifts.